Kajian Pengelolaan Ekowisata di Desa Bendosari Kecamatan Pujon Kabupaten Malang - Raja, Antonius Kasa; Alfian, Rizki; Djoko, Riyanto (Jurnal Arsitektur Lansekap, 2021)
Study of Ecotourism Management in Bendosari Village, Pujon District, Malang Regency. The concept of ecotourism is one alternative to develop an area into a tourist destination that pays attention to environmental sustainability by utilizing the potential of natural and cultural resources of the local community. Therefore, the existence of the concept of ecotourism can ensure the preservation of nature and its ecosystem. This study aims to: 1) Identify the potential and problems in Bendosari Village, Pujon District, Malang Regency, 2) Identify the feasibility level of ecotourism in Bendosari Village, Pujon District, Malang Regency, and 3) Develop a strategy for developing ecotourism areas in Bendosari Village, Pujon District, Malang Regency. Collecting data in this study using survey methods (observations and interviews), literature study and documentation methods. Analysis of the data used, namely: first qualitative descriptive analysis, second feasibility analysis based on the Guidelines (ADO-ODTWA) of the Director General of PHKA 2003 and the last is SWOT analysis. The results showed that: 1) The potential of natural resources in the ecotourism area of Bendosari Village, namely: the potential for flora and fauna, the potential for nature tourism, the potential for educational tourism, the potential for craft tourism and the potential for cultural tourism. The problems of ecotourism in Bendosari Village include the low quality of human resources, limited funds and the role of the Malang Regency Government which has not been active. 2) Ecotourism in Bendosari Village is feasible to be developed as a tourist attraction with the results of the Guideline assessment (ADO-ODTWA) of 82.71%. 3) The strategy for developing Ecotourism in Bendosari Village is an expansion strategy (supporting offensive strategies) with alternative strategies that include: maximizing the development of ecotourism packages, empowering local communities in ecotourism activities, increasing security in tourist attractions, and maximizing tourism potential management.